Comparison of outcomes following three surgical techniques for patients with severe jejunoileal atresia. (4th July 2019) - Peng, Yan-Fen; Zheng, Hai-Qing; Zhang, Hong; He, Qiu-Ming; Wang, Zhe; Zhong, Wei; Yu, Jia-Kang
Abstract: Background: Severe jejunoileal atresia is associated with prolonged parenteral nutrition, higher mortality and secondary surgery. However, the ideal surgical management of this condition remains controversial. This study aimed to compare the outcomes of patients with severe jejunoileal atresia treated by three different procedures. Methods: From January 2007 to December 2016, 105 neonates with severe jejunoileal atresia were retrospectively reviewed. Of these, 42 patients (40.0%) underwent the Bishop–Koop procedure (BK group), 49 (46.7%) underwent primary anastomosis (PA group) and 14 (13.3%) underwent Mikulicz double-barreled ileostomy (DB group). Demographics, treatment and outcomes including mortality, morbidity and nutrition status were reviewed and were compared among the three groups. Results: The total mortality rate was 6.7%, showing no statistical difference among the three groups ( P  =   0.164). The BK group had the lowest post-operative complication rate (33.3% vs 65.3% for the PA group and 71.4% for the DB group, P  =   0.003) and re-operation rate (4.8% vs 38.8% for the PA group and 14.3% for the DB group, P  <   0.001). Compared with the BK group, the PA group showed a positive correlation with the complication rate and re-operation rate, with an odds ratio of 4.15 [95% confidence interval (CI): 1.57, 10.96] and 12.78 (95% CI: 2.58, 63.29), respectively. The DB group showed a positive correlation with the complication rate when compared with the BK group, with an odds ratio of 7.73 (95% CI: 1.67, 35.72). The weight-for-age Z-score at stoma closure was –1.22 (95% CI: –1.91, –0.54) in the BK group and –2.84 (95% CI: –4.28, –1.40) in the DB group ( P  =   0.039). Conclusions: The Bishop–Koop procedure for severe jejunoileal atresia had a low complication rate and re-operation rate, and the nutrition status at stoma closure was superior to double-barreled enterostomy. The Bishop–Koop procedure seems to be an appropriate choice for severe jejunoileal atresia.